Network security tools-firewall / Ding Khoon Chong - Ding, Khoon Chong (2005)
A firewall is a system or group of systems that enforces an access control policy between two or more networks. The actual means by which this is accomplished varies widely, but in principle, the firewall can be thought of as pair of mechanisms: one which exists to block traffic, and the other which exists to permit traffic. Some firewall place a greater emphasis on blocking traffic, while others emphasize permitting traffic. Probably the most important thing to recognize about a firewall is that it implements an access control policy. If we do not have a good idea of what kind of access you want to allow or to deny, a firewall really would not help you. It i also important to recognize that the firewall's configuration because it is a mechanism for enforcing policy, imposes its policy on everything behind it. Administrators for firewalls managing the connectivity for a large number of hosts therefore have a heavy responsibility.